Basic Concepts of Oxide Gold Deposits and the Role of Mineralogy - E. Daniel Baker (The Minerals, Metals and Materials Society, 1997)
"The term ""oxide disseminated gold deposits"" refers to near surface, gold-bearing veins, faults, and shear zones that typically contain appreciable amounts of oxidized ore or gossanous material, resulting from oxidation of sulphides.The concept of oxide gold deposits underwent a dramatic change after the discovery of the Carlin gold mine in north-central Nevada in the early 1960's. Now the term implies large tonnage, low-grade bulk minable deposits that are processed by milling and/or heap leach methods.Oxide gold deposits may now be classified into two types: (1) primacy ores derived directly from the effects of hydrothermal alteration on host rocks, and (2) secondary oxide ores derived from the supergene oxidizing effects of circulating post-mineral meteoric waters on gold-bearing sulphides. Each type of deposit has unique diagnostic mineralogic and metallurgical characteristics that must be addressed to achieve successful exploration strategies and viable metallurgical exploitation.The author would like to thank the management of Newmont Metallurgical Services and Newmont Mining Company for allowing presentation of this paper. Thanks are due Sevkett Acar, Donald M. Hausen, Jerry R. Odekirk, and D. Erik Spiller for their critical review of the manuscript. Also, thanks are extended to all those cited and uncited whose hard work and dedication have led to the discovery and exploitation of near-surface oxide gold deposits. Our knowledge would be greatly limited without the dedication and research of many others."